solve by substitution: x=5y - 2, 2x + y = -4  TOPIC_SOLVED

Simplificatation, evaluation, linear equations, linear graphs, linear inequalities, basic word problems, etc.

solve by substitution: x=5y - 2, 2x + y = -4

Postby buddy on Sun Mar 01, 2009 10:21 pm

Solve the system using the substituation method...
x=5y - 2
2x + y = -4
not sure of what im doing?
buddy
 
Posts: 135
Joined: Sun Feb 22, 2009 10:05 pm

Sponsor

Sponsor
 

  TOPIC_SOLVED

Postby stapel_eliz on Sun Mar 01, 2009 10:52 pm

buddy wrote:Solve the system using the substituation method...
x=5y - 2
2x + y = -4
not sure of what im doing?

To "solve by substitution", you substitute from one equation into the other. In your case, the first equation is already solved for "x=", so plug the other side of that equation, the "5x - 2", in for the "x" in the second equation:

. . . . .2(5y - 2) + y = -4

Can you take it from there? :wink:
User avatar
stapel_eliz
 
Posts: 1718
Joined: Mon Dec 08, 2008 4:22 pm

Re: solve by substitution: x=5y - 2, 2x + y = -4

Postby buddy on Mon Mar 02, 2009 6:45 pm

y=0
x=0-2=-2
thnx
buddy
 
Posts: 135
Joined: Sun Feb 22, 2009 10:05 pm


Return to Beginning Algebra